2016
DOI: 10.1016/j.apsusc.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Improving the work function of the niobium surface of SRF cavities by plasma processing

Abstract: An in-situ plasma processing technique using chemically reactive oxygen plasma to remove hydrocarbons from superconducting radio frequency cavity surfaces at room temperature has been developed at the spallation neutron source, at Oak Ridge national laboratory. To understand better the interaction between the plasma and niobium surface, surface studies on small samples were performed. In this article, we report the results from those surface studies. The results show that plasma processing removes hydrocarbons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Plasma mineralization with volume DBD showed spots of inhomogeneity in the distribution of carbon. [44][45][46] Therefore, work function of the mesoporous TiO 2 coating could be affected by the carbon concentration of the surface, which was efficiently influenced by plasma mineralization with both DBDs. After plasma mineralization with volume DBD, the difference between the maximum and the minimum of the carbon concentration was approx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma mineralization with volume DBD showed spots of inhomogeneity in the distribution of carbon. [44][45][46] Therefore, work function of the mesoporous TiO 2 coating could be affected by the carbon concentration of the surface, which was efficiently influenced by plasma mineralization with both DBDs. After plasma mineralization with volume DBD, the difference between the maximum and the minimum of the carbon concentration was approx.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, plasma surface modification can affect the morphology and chemistry of the surface by etching, contamination removal, and incorporation of functional groups onto the surface. [44][45][46] Therefore, work function of the mesoporous TiO 2 coating could be affected by the carbon concentration of the surface, which was efficiently influenced by plasma mineralization with both DBDs. The coplanar DBD led to a lower carbon concentration and thus a higher work function.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, when Ar/O 2 mixed plasma was used, the work function increased quickly from 4.0 to 5.2 eV after 30 s of plasma cleaning, then leveled off, indicating that the addition of O 2 can accelerate the removal of hydrocarbon pollutants and may further oxidize the niobium surface when compared to pure Ar plasma cleaning. To further demonstrate that chemical reactions occurred on the surface following Ar/O 2 mixed plasma treatment, EQP was used to monitor CO 2 and CO [ 23,24 ] as byproducts in the plasma cleaning process, as shown in Figure 2B. The EQP test plays a monitoring role.…”
Section: Treatment Mechanism Of Multicomponent Plasmamentioning
confidence: 99%
“…In-situ processing of SRF cavities in the tunnel has been identified as an important area of research to improve the performances of SNS SRF cavities while minimizing the impact on machine operation and reducing cost for the improvements. R&D for in-situ processing using plasma has successfully demonstrated that the accelerating gradients in operating cavities can be increased by 2 MV/m or higher on average [31,32]. The plasma processing developed at the SNS mainly focuses on removal of residual hydro-carbons using low density reactive oxygen plasma at room temperature.…”
Section: Srf Cavity Performance Improvementmentioning
confidence: 99%